EFL LEARNERS’ SELF-EFFICACY IN PUBLIC SPEAKING CLASS DURING ONLINE LEARNING - Wahyuni, Sri Rizki; Suryani, Hilma; Mesalina, Juliana (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2023)
This study examines EFL Learners' Self-Efficacy in Public Speaking Class while enrolled in online classes. The researchers conducted quantitative survey research. The study was carried out in September 2022, and data was gathered through the use of a questionnaire. Paradewari's (2017) research was used to create the questionnaire. The survey included 70 students from the English Education Study Program at Sulthan Thaha Saifuddin State Islamic University in Jambi. The questionnaire is a closed questionnaire with 20 questions that will be used to collect data more efficiently. The study's findings indicate that students have high self-efficacy after completing public speaking classes, and they are comfortable speaking in front of large groups of people. Furthermore, self-efficacy affects not only public speaking courses but also other courses.